Social Reformism 2.0 Work, Welfare and Progressive Politics in the 21st Century - Ferrera, Maurizio (Edward Elgar Publishing, 2023)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Automation, digitalisation, the post-industrial transition and climate change are creating new social risks which are not adequately supported by established welfare state institutions. In this timely book, Maurizio Ferrera, Joan Miró and Stefano Ronchi propose critical social and institutional policy reform in response to the nation state's inability to maintain a balanced ecosystem between democracy, the market economy, welfare and the rule of law.